2019
DOI: 10.1108/md-02-2019-0233
|View full text |Cite
|
Sign up to set email alerts
|

Newcomer retention – an investigation on Indian IT industry

Abstract: Purpose Understanding attrition in this VUCA world has become imperative for organizations to ensure they are able to sustain themselves. While focus on understanding attrition is important, it is equally important to retain acquired talent, at the same time add value to the human side of business. The purpose of this paper is to explore the factors which play crucial role in retention of newly hired employees working in Indian IT industry. The study has considered factors, namely, supervisor support behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…This becomes more important in our case as 66% of our sampled population were below 32 years. Prior research on young IT professionals has shown negative effect of supervisory support behaviours on employees' intention to quite (Deshpande and Gupta, 2019). The informal support extended by managers as well as friendly colleagues help youngsters get firmly embedded in the organization and mature in their domain expertise.…”
Section: Discussionmentioning
confidence: 99%
“…This becomes more important in our case as 66% of our sampled population were below 32 years. Prior research on young IT professionals has shown negative effect of supervisory support behaviours on employees' intention to quite (Deshpande and Gupta, 2019). The informal support extended by managers as well as friendly colleagues help youngsters get firmly embedded in the organization and mature in their domain expertise.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, promoting experiences that lead to mastery, achieving work goals, stimulating self-growth, and achieving superior job performance is possible when job demands are efficiently optimized or dealt with (Bakker and Demerouti, 2017; Bakker and de Vries, 2021). Additionally, continuing training/coaching, communicating the company vision, and supporting supervisors may lead to positive social interactions and relational networks in the context of IT projects (Deshpande and Gupta, 2019; Jiang et al , 2020). Thus, supervisors still need to inspire and encourage their subordinates to take personal responsibility for their performance or to craft their own working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, global business activities are rapidly increasing, where there is heavy dependence on electronic devices to record every transaction and increased reliance on IT-related service projects provided by professional service firms to cope with the complexity of the business environment. It is reasonable to infer that improving IT employees' job satisfaction and organizational commitment is a strong determinant of project success (Deshpande and Gupta, 2019; Park et al , 2020). Therefore, supervisors should provide needed support to their subordinates to reduce perceived job demands and increase job resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, their inclination towards social interactions (Huo and Jiang, 2023) simplifies seeking feedback in the workplace. Through feedback seeking, employees can gather information to adapt their behavior, considering their job and personal characteristics, for optimal performance and motivation (Deshpande and Gupta, 2021). FSB not only helps individuals cope with job demands and challenges but also mitigates burnout (Bouckenooghe et al, 2022).…”
Section: Performance Pressure and Fsb -Moderating Role Of Extraversionmentioning
confidence: 99%